Bone response to biomimetic implants delivering BMP-2 and VEGF: An immunohistochemical study - Ramazanoglu, Mustafa; Lutz, Rainer; Rusche, Philipp; Trabzon, Levent; Kose, Gamze Torun; Prechtl, Christopher; Schlegel, Karl Andreas (Journal of Cranio-Maxillofacial Surgery, 2013)
This animal study evaluated bone healing around titanium implant surfaces biomimetically coated with bone morphogenic protein-2 (BMP-2) and/or vascular endothelial growth factor (VEGF) by examining bone matrix proteins and mineralisation. Five different implant surfaces were established: acid-etched surface (AE), biomimetic calcium phosphate surface (CAP), BMP-2 loaded CAP surface, VEGF loaded CAP surface and dual BMP-2 + VEGF loaded CAP surface. The implants were inserted into calvariae of adult domestic pigs. For the comparison of osteoconductive capacity of each surface, bone mineral density and expression of bone matrix proteins (collagen I, BMP-2/4, osteocalcin and osteopontin) inside defined chambers around the implant were assessed using light microscopy and microradiography and immunohistochemical analysis at 1, 2 and 4 weeks. In the both groups delivering BMP-2, the bone mineral density was significantly enhanced after 2 weeks and the highest value was measured for the group BMP + VEGF. In the group VEGF, collagen I and BMP-2/4 expressions were significantly up-regulated at the first and second weeks. The percentage of BMP-2/4 positive cells in the group BMP + VEGF was significantly enhanced compared with the groups AE and CAP at the second week. Although the highest osteocalcin and osteopontin expression values were observed for the group BMP + VEGF after 2 weeks, no statistically significant difference in osteocalcin and osteopontin expressions was found between all groups at any time. It was concluded that combined delivery of BMP-2 and VEGF favoured bone mineralisation and expression of important bone matrix proteins that might explain synergistic interaction between both growth factors. © 2013 European Association for Cranio-Maxillo-Facial Surgery. Published by Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2024-05-13
Keywords: Biomimetic; Bone; Bone morphogenic protein (BMP); Immunohistochemistry; Osteoconductivity; Vascular endothelial growth factor (VEGF)